1996
DOI: 10.1037/0022-0663.88.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and attention in the classroom: An interaction between past and present academic experiences.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
14
0
3
Order By: Relevance
“…For instance, it has been shown that positive feedback yields more beneficial effects if the positive feedback (a) is communicated in an autonomy-supporting rather than a controlling way (Ryan, 1982); (b) is perceived as honest; (c) is focused on selfreferenced improvement rather than on normative performance (Butler, 1987); (d) is referring to successful attempts for tasks that are specific and realistic (Henderlong & Lepper, 2002); and (e) if the feedback provider is perceived as prestigious, trustworthy, and proficient (Bandura, 1977). Accordingly, the effects of feedback on motivation may be moderated by recipients' characteristics, such as self-esteem (Smith & Smoll, 1990), self-efficacy (Nease, Mudgett, & Quiñones, 1999), selfhandicapping (Thompson, 2004), previous levels of performance (Monteil, Brunot, & Huguet, 1996), and personal achievement goal orientation (Elliott, Shell, Henry, & Maier, 2005). What remained relatively unexplored in the feedback literature, however, is the way in which corrective feedback can be communicated and what the consequences are of different communication styles.…”
Section: The Motivating Role Of Feedbackmentioning
confidence: 99%
“…For instance, it has been shown that positive feedback yields more beneficial effects if the positive feedback (a) is communicated in an autonomy-supporting rather than a controlling way (Ryan, 1982); (b) is perceived as honest; (c) is focused on selfreferenced improvement rather than on normative performance (Butler, 1987); (d) is referring to successful attempts for tasks that are specific and realistic (Henderlong & Lepper, 2002); and (e) if the feedback provider is perceived as prestigious, trustworthy, and proficient (Bandura, 1977). Accordingly, the effects of feedback on motivation may be moderated by recipients' characteristics, such as self-esteem (Smith & Smoll, 1990), self-efficacy (Nease, Mudgett, & Quiñones, 1999), selfhandicapping (Thompson, 2004), previous levels of performance (Monteil, Brunot, & Huguet, 1996), and personal achievement goal orientation (Elliott, Shell, Henry, & Maier, 2005). What remained relatively unexplored in the feedback literature, however, is the way in which corrective feedback can be communicated and what the consequences are of different communication styles.…”
Section: The Motivating Role Of Feedbackmentioning
confidence: 99%
“…Studies on the consistency between an individual's position in the current situation (being recognized as a high or low achiever in a bogus task) and his/her usual position (having a high or low academic standing as a general rule) showed that in situations where these two positions differed, students seemed to devote part of their attention to thinking about the meaning of this unusual situation (Brunot, Huguet, & Monteil, 2000;Kluger & DeNisi, 1996;Monteil, Brunot, & Huguet, 1996). Consequently, performance observed in this ''inconsistent'' situation was lower than that found in a ''consistent'' situation.…”
Section: Discussionmentioning
confidence: 97%
“…In the first experiment, only the fictitious position of expertise assigned to the participants was manipulated. In the second experiment, actual expertise (academic standing) and fictitious expertise were manipulated simultaneously, based on the finding that performance may depend on an interaction between these two variables (e.g., Brunot, Huguet, & Monteil, 2000;Kluger & DeNisi, 1996;Monteil, 1991;Monteil, Brunot, & Huguet, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Los estudiantes que poseen una historia académica positiva, que creen en sí mismos, con la práctica desarrollan un sentido creciente de competencia. Para que un estudiante tenga éxito académico, entendido éste como comprometerse en una actividad, mantener interés, sostener conductas de esfuerzo, persistencia en el trabajo y avanzar en el logro de sus metas, no sólo requiere disponer de potencial intelectual, sino haber desarrollado competencias para el trabajo académico unidas a un sistema de creencias orientadas al logro (Hayamizu y Weiner, 1991;Monteil, Brunot y Huguet, 1996).…”
Section: Aspectos Motivacionalesunclassified